Perbandingan Jenis Cairan Rehidrasi terhadap Tingkat Dehidrasi dan VO2 Maksimal pada Remaja Putri Peserta Ekstrakurikuler Bola Basket - Nissa, Choirun; Madjid, Indah Juliana; Januardo, Ferdian Hapreda (Jurnal Gizi, 2021)
Indonesia currently tends to have fluctuative achievement in sports, especially in basketball. The sports performance can be affected by several things, which are relatedto the fulfillment of nutritional adequacy. Balance of fluid is one of essential intakes forathletes. This study aimed to analyze the comparison of rehydration fluids type todehydration level and vo2max on female teens of basketball extracurricular participants.This study design was quasy experiment with posttest only group design. Thetreatments in this study were divided into 3 groups, the first is water-given group, thesecond water-CHO 6%-given group and the third is isotonic water-given group. Alltreatments were performed to 8 female teens of basketball extracurricular participantson the different days. The results of Kruskal-Wallis statistical test showed difference in the level ofdehydration in a variety of treatments (p = 0.0001). Based One Way Anova there wereno differences in the various treatments VO2max (p = 0.180). The conclusion of thisresearch was that providing isotonic water could help reach the best level of hydrationfor an athlete during training. Key words: Dehydration Level, VO2max, Rehydration Fluid